2020
DOI: 10.3390/app10134451
|View full text |Cite
|
Sign up to set email alerts
|

A Simplified Method for Real-Time Prediction of Temperature in Mass Concrete at Early Age

Abstract: According to the practice of temperature control in dam concrete, within a few days after a concrete block is poured, the temperature at the core of the concrete rises rapidly. The maximum temperature may still exceed the standard even under a relatively perfect post-cooling system, which is mostly caused by failure to quickly and correctly judge the development of the early-age temperature. This study investigates concrete temperature at an early age via in situ monitoring data collected from Baihetan arch da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…Statistical analyses-such as data regression [37][38][39][40] and autoregressive integrated moving average (ARIMA) [41] of historical monitoring data can be used to develop bestfit models (i.e., equations or formulas) for predicting concrete temperature changes in similar scenarios. This simple and rapid method is widely used in dams [37] , bridges [38,40] , and other concrete structures. For periodic temperature prediction, the ARIMA can also be used to develop prediction models [41] .…”
Section: Prediction Methodsmentioning
confidence: 99%
“…Statistical analyses-such as data regression [37][38][39][40] and autoregressive integrated moving average (ARIMA) [41] of historical monitoring data can be used to develop bestfit models (i.e., equations or formulas) for predicting concrete temperature changes in similar scenarios. This simple and rapid method is widely used in dams [37] , bridges [38,40] , and other concrete structures. For periodic temperature prediction, the ARIMA can also be used to develop prediction models [41] .…”
Section: Prediction Methodsmentioning
confidence: 99%
“…During the construction period, the temperature field of the dam body is affected by multiple factors, such as cement hydration heat, artificial cooling, and ambient temperature. In the stage of operation, cement hydration heat has basically dissipated, and the temperature field is affected by ambient temperature, e.g., air temperature and water temperature [43][44][45][46]. Concrete temperature has a significant impact on the stability of the dam during the construction period, but its effects during regular operation afterward are essentially insignificant.…”
Section: Tfe Constructionmentioning
confidence: 99%
“…The results showed that: the prediction of temperature distribution in concrete by the three-dimensional model was relatively accurate, with an error of less than 4%; the surface temperature difference in July was twice as much as that in December; the wind speed had a cooling effect on the surface of the concrete, and the larger the wind speed was, the stronger the cooling effect was. Guo An [25] et al analyzed the on-site temperature monitoring data collected by the engineering examples, and obtained an empirical formula for calculating the cooling effect of the concrete, by combining The results of measured data and empirical formula was compared and analyzed, and it was found that the empirical formula had better calculation effect, and the equation of the rate of temperature rise of the heat of hydration was derived. LiBao Yui [26] et al, in order to predict the trend of temperature change of mass concrete, constructed a CART prediction model based on the technology of large-data processing, and the results of the study showed that the model and the method can predict the temperature change of the mass concrete better, and the prediction accuracy is higher, and can be used for practical purposes.…”
Section: Introductionmentioning
confidence: 99%